2021
DOI: 10.11606/s1518-8787.2021055003069
|View full text |Cite
|
Sign up to set email alerts
|

Violência sexual em mulheres na Amazônia Ocidental

Abstract: OBJETIVO: Caracterizar os casos de violência sexual sofridos por mulheres notificadas pelo Sistema de Informação de Agravos de Notificação no município de Rio Branco (AC) no período de 2011 a 2016. MÉTODOS: Estudo descritivo com base nas informações do Sistema de Informação de Agravos de Notificação. A população do estudo foi constituída por mulheres vítimas de violência sexual notificadas no município de Rio Branco (AC), de 2011 a 2016. RESULTADOS: Os resultados da investigação apresentam maior número de noti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
4
0
2
Order By: Relevance
“…O número elevado em estados da região norte do país está relacionado com a dificuldade de realizar estudos e discussões com a população sobre o tema, esses obstáculos se apresentam desde a grande extensão territorial, aliada ao difícil acesso de determinados pontos, até condições socioeconômicas precárias de boa parte dos habitantes (Cargnin et al, 2021).…”
Section: Aspectos Do Abuso Sexual Infantilunclassified
“…O número elevado em estados da região norte do país está relacionado com a dificuldade de realizar estudos e discussões com a população sobre o tema, esses obstáculos se apresentam desde a grande extensão territorial, aliada ao difícil acesso de determinados pontos, até condições socioeconômicas precárias de boa parte dos habitantes (Cargnin et al, 2021).…”
Section: Aspectos Do Abuso Sexual Infantilunclassified
“…Erin Clifton, publishes about colposcopy in 2020, and defines it as a sensitive technique for subtle genital lesions, and that there are currently colposcopes with a camera which allows detecting and capturing photographs of the lesions found; In addition, toluidine blue is usually used on lesions and then presented as evidence. (28) In the studies carried out by Vandeven, she mentions that colposcopy is useful in 87% of lesions compared to macroscopic inspection with 40% usefulness. (29) Staining techniques in colposcopy at the vaginal level are used through solutions, and the most common is toluidine to detect lacerations in mucous membranes that cannot be identified macroscopically, which is why Zilkens R, in 2017, performed A study revealed that the combination of these techniques favors 97%, while the use of toluidine staining without a colposcope gives an effectiveness of 40 to 58%.…”
Section: Colposcopementioning
confidence: 99%
“…In order to demonstrate the presence of semen in the rectal area, it is necessary to do so immediately after the violation, since if a fecal bowel movement is performed, it can be expelled through contractions and the release of feces; But a sample of feces must also be looked for in the attacker's genital area, because if I do not use protection, it may prove guilt. (28) In addition, a search is also carried out for remains of organic tissues that may be found as a result of scratches to the sexual offender, presence of pubic hairs, loose or torn hairs which may also be covered with fluid, be it semen, vaginal secretion or blood; Therefore, hair collection is necessary. ( 29)…”
Section: Rectal Swabmentioning
confidence: 99%
See 2 more Smart Citations